Identification of Heme Propionate Vibrational Modes in the Resonance Raman Spectra of Cytochrome c Oxidase - Egawa, Tsuyoshi (2009)
The propionate groups of heme a and a(3) in cytochrome c oxidase (CcO), have been postulated to mediate both the electron and proton transfer within the enzyme. To establish structural markers for the propionate groups, their associated vibrational modes were identified in the resonance Raman spectra of CcO from bovine (bCcO) and Rhodobacter sphaeroides (RsCcO). The distinction between the modes from the propionates of heme a and heme a(3), as well as those from the propionates on the pyrrole rings A and D in each heme, was made on the basis of H(2)O-D(2)O isotope substitution experiments, combined with wavelength-selective resonance enhancement (for bCcO) or mutagenesis studies (for RsCcO).